Pseudomelanoma on hypertrophic scar. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2010)
Pseudomelanoma -or recurrent nevus or persistent nevus- is the reappearance of melanic pigment in the site of accidental or therapeutical removal of a nevus. This is believed to occur thanks to the rise upwards of melanocytes from a deep residual component of the nevus or from hair follicles. In case of linear scars, both spontaneous or more frequently surgical, pseudomelanoma acquires a characteristic linear look, perpendicular to the longer axis of the scar (1, 2). On dermoscopy, in the latter case pseudomelanoma consists of linear, parallel pigmentations, which are reminiscent of acral pattern. The superficial collagen bundles of the dermis, which join the two lips of the wound, are responsible for this characteristic look of pseudomelanoma.